TRIM21, a New Component of the TRAIL-Induced Endogenous Necrosome Complex - Simoes Eugénio, Mélanie; Faurez, Florence; Kara-Ali, Ghania H.; Lagarrigue, Mélanie; Uhart, Perrine; Bonnet, Marion C.; Gallais, Isabelle; Com, Emmanuelle; Pineau, Charles; Samson, Michel; Le Seyec, Jacques; Dimanche-Boitrel, Marie-Thérèse (Frontiers in Molecular Biosciences, 2021)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a well-known apoptosis inducer and a potential anticancer agent. When caspases and inhibitors of apoptosis proteins (IAPs) are inhibited, TRAIL induces necroptosis. Molecular mechanisms of necroptosis rely on kinase activation, and on the formation of a necrosome complex, bringing together the receptor-interacting protein kinases 1 and 3 (RIPK1, RIPK3), and the mixed lineage kinase domain-like protein (MLKL). In this study, mass spectrometry approach allowed to identify the tripartite motif containing 21 (TRIM21), an E3 ubiquitin-protein ligase as a new partner of the endogenous TRAIL-induced necrosome. Alteration of TRIM21 expression level, obtained by transient transfection of HT29 or HaCat cells with TRIM21-targeted siRNAs or cDNA plasmids coding for TRIM21 demonstrated that TRIM21 is a positive regulator of TRAIL-induced necroptosis. Furthermore, the invalidation of TRIM21 expression in HT29 cells by CRISPR-Cas9 technology also decreased cell sensitivity to TRAIL-induced necroptosis, a shortcoming associated with a reduction in MLKL phosphorylation, the necroptosis executioner. Thus, TRIM21 emerged as a new partner of the TRAIL-induced necrosome that positively regulates the necroptosis process.